필로티 반자 내 화재 시 단열재 화염확산 특성연구 - 김홍식(Hong-Sik Kim); 오부열(Bu-Yeol Oh); 박민영(Min-Young Park) (한국화재소방학회 논문지, 34(5), 2020)
본 논문에서는 필로티 구조 건축물의 천장(반자 위) 공간 내부를 모사한 축소모형과 실대화재 실험을 통해 천장(반자 위) 단열재, 천장재에 따른 화재확산의 정도, 시간에 따른 온도변화를 확인하였다. 축소모형 실험의 천장공간내부구조는 압출법 단열재(XPS 단열재) + 열경화성수지 천장재(SMC), 난연 비드법 단열재(난연 EPS) + 열경화성수지 천장재(SMC), 그리고 압출법 단열재(XPS) + 아연도금강판 천장재(DMC)로 예비실험을 진행하였다. 이를 바탕으로 필로티 구조 건축물 화재를 모사한 실대화재 실험을 통해 천장(반자 위) 내부 공간에서의 열의 유동 파악, 대형화재로의 확산 원인을 확인하였다. 실대화재 실험은 화재 사고를 가정하여 최상의 경우인 난연 EPS 단열재 + DMC천장재와 최악의 경우인 XPS 단열재 + SMC 천장재로 진행하였다. 실험결과, 화원에 노출된 단열재에서부터 연소가시작되어 용융된 압출법 단열재(XPS)가 열결화성수지 천장재(SMC)로 낙하하면서 새로운 화원을 형성하고 천장재가탈락하며 산소 유입에 의해 연소 확대로 이어졌다. In piloti-type structures, large-scale fires frequently occur because insulation materials in the ceiling are ignited. However,the spread of fire in these cases is not well known. Therefore, this study conducted small-scale (1.0 m × 1.0 m) tests andreal-scale model tests. According to the results, we clarified the fire spread, temperature variation over time, and the effectsof insulation materials in fire sites. For the small-scale tests, the internal structure of the ceiling was extruded polystyrene(XPS) + sheet molding compound (SMC), retardant expanded polystyrene (Retardant EPS) + sheet molding compound(SMC), and extruded polystyrene (XPS) + design metal ceiling (DMC). From the small-scale and large-scale tests thatsimulated a fire in a piloti-type structure, the flow of heat in the interior space and the cause of a large fire were identified. The tests were conducted with EPS+DMC, defined as the best-case scenario, and XPS+SMC, defined as the worst-casescenario during a fire accident. The results from the tests showed that combustion began when the insulation material wasexposed to the fire source. Then, molten XPS fell onto the SMC, establishing a new fire source that destroyed the ceilingmaterial, leading to increased combustion due to the inflow of oxygen. KCI Citation Count: 0